2002
DOI: 10.1016/s0378-4371(02)00736-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the social network of scientific collaborations

Abstract: The co-authorship network of scientists represents a prototype of complex evolving networks. By mapping the electronic database containing all relevant journals in mathematics and neuro-science for an eight-year period (1991-98), we infer the dynamic and the structural mechanisms that govern the evolution and topology of this complex system. First, empirical measurements allow us to uncover the topological measures that characterize the network at a given moment, as well as the time evolution of these quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
1,572
7
133

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,199 publications
(1,754 citation statements)
references
References 36 publications
42
1,572
7
133
Order By: Relevance
“…Previous studies have demonstrated that scientific communities and research groups endure longer if they have a strong, active nucleus of members, suggesting that a stable core of investigators is fundamental to ensuring the longterm sustainability of the groups. More importantly, these authors play an important role in terms of cultivating the scientific community and integrating new members (WU et al 2009;BARABASI et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that scientific communities and research groups endure longer if they have a strong, active nucleus of members, suggesting that a stable core of investigators is fundamental to ensuring the longterm sustainability of the groups. More importantly, these authors play an important role in terms of cultivating the scientific community and integrating new members (WU et al 2009;BARABASI et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, they can describe the degree of interaction and the influence of different agents or groups within the research community (GONZÁLEZ ALCAIDE et al 2010;NEWMAN 2001). The use of SNA has seen considerable development in the past several years (MELIN & PERSSON 1996), complementing and deepening the initial approaches taken since the 1960s in the field of bibliometrics (first by PRICE and then by CRANE) in relation to the concept of "invisible colleges" and the analysis of citation and co-citation networks (BARABASI et al 2002;CRANE 1969;MULLINS 1980;PRICE 1965;PRICE 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Tanto que, ao observar as redes nas quais os atores são os docentes e/ou pesquisadores e as conexões entre eles são evidenciadas pela partilha de autoria de trabalhos de pesquisa (A. Silva, Matheus, Parreiras, & Parreiras, 2006;Barabási et al, 2002;Newman, 2001a), percebe-se que o progresso da ciência depende -de forma preponderante -dessas associações (Autry & Griffis, 2005).…”
Section: Um Cenário De Relações De Competição E Colaboração Concomitaunclassified
“…First, collaborative networks have been widely used in scientometrics and social networks studies. Second, collaboration networks have been known to possess many static and dynamic properties that are similar to other social networks (Barabasi et al, 2002;Newman, 2004).…”
Section: Observations and Motivationsmentioning
confidence: 99%
“…Many real-world complex networks have been shown to exhibit a common set of properties. The properties include power-law degree distributions (Barabasi, 2003), the small world effect (Barabasi, 2003), assortative mixing Redner, 2008), and kinetic properties exhibited in the growing process of social networks (Barabasi et al, 2002;Kumar et al, 2006;Leskovec et al, 2005), e.g., the shrinking diameter phenomenon. These properties in real networks represent a significant departure from random networks (Bollobas, 2001).…”
Section: Introductionmentioning
confidence: 99%